Development of Interactive Learning Media Canva Based on Virus Material at High School - Delsa Mahmudah; Marlinda Nilan Sari Rangkuti (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Virus material in biology subjects is abstract and often difficult for students to understand, which results in low effectiveness of the learning process in the classroom. This study aims to develop Canva-based interactive learning media on virus material, as well as to test its feasibility, practicality, and effectiveness in improving student learning outcomes. This research is development research (R&D) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects included material experts, media experts, learning experts, biology teachers, and grade X students at High School 1 Labuhan Deli. Data was collected through interviews, questionnaires, and learning outcome tests (pretest and posttest), which were then analyzed descriptively, qualitatively, and quantitatively. The research findings indicated that this Canva-based learning media is categorized as